DEVELOPMENTAL PROSPECTIVE ANALYSIS OF LIVESTOCK POPULATION AND SUITABILITY OF GOAT FARMING IN TIRUVARUR DISTRICT OF TAMIL NADU - V. Sujatha; P. Selvaraj; V. Leela; M. Ramachandran; V. Ranganathan; T.C. Balamurugan; M. Kathirchelvan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was planned to analyze the changes in livestock population growth rates and its trends in Tiruvarur district. Tiruvarur shares 2.94 per cent of goat and 2.1 per cent of cattle population to the respective population of Tamil Nadu. The remaining livestock species (buffalo, sheep, pig and poultry) including poultry share of Tiruvarur to states respective species population was negligible, contributing less than one per cent. Recent 20th census, evinced a positive growth rate with highest favourable growth rate of 64.65 per cent for poultry, followed by 2.3 per cent in cattle and 1.44 per cent for goat population of Tiruvarur. Negative growth rates were recorded for other species, which was found to be similar to the state population growth trend. Tiruvarur had a decrease in total livestock population and species-wise too showing negative growth rates between inter census period. Percentage population change over from the base year was 3.23% for goat whereas this was on negative trend for all other species. Analyzing the compositional share of livestock population, goat had the highest share with 53.03±2.62 per cent. All other livestock showed a decreasing trend from 16th to 20th census in Tiruvarur livestock population change. Inadequate infrastructure facilities (77.3%) topped among the five constraints analysed, followed by non-availability of feeds and fodders, mortality and environmental factors. Least constraint was found to be marketing facility. It can be concluded that increasing demand for goat meat, which fetch high remunerative price along with easy managemental practices and favorable conducive environment than other livestock, makes goat farming a highly suitable farming system for Tiruvarur.